Antimicrobial stewardship program in public hospitals: Perception and preparedness of pharmacists / Nur Hidayah Kamaruzaman - Kamaruzaman, Nur Hidayah (2015)
Antimicrobial Stewardship Program has long been identified by most society in Infectious Disease field as an effective measure to promote appropriate utilization of antimicrobial agents as well as to curb antimicrobial resistance especially in developed countries. However, less is known about the practice of antimicrobial agents among pharmacists in Malaysian public hospitals and their awareness towards this program. Hence, this study is conducted to evaluate the perception, attitudes and awareness of pharmacists in public hospitals on the issue of antimicrobial resistance and the principles of antimicrobial stewardship. A qualitative, cross-sectional study was carried out among pharmacists in 3 public hospitals in Selangor and Kuala Lumpur with an established practice of AMS for at least 3 years, using a validated questionnaire that consisted of 6 domains with 59 items. 180 pharmacists were recruited in this study from all three study sites with overall response rate of 56.4%. Data were analysed using SPSS version 19 software for Windows, using descriptive and appropriate non-parametric tests. From 180 pharmacists recruited in this study, majority were found to be fully registered pharmacists (82.2%), has been working for 1 to 3 years (33.3%) and possessed at least a bachelor degree in pharmacy (89.4%). In terms of pharmacists' perception towards the issue of antimicrobial resistance, it was found that the cumulative mean scores of respondents were 44.2 (SD±3.95). On the other hand, the mean scores for knowledge on goals and activities of Antimicrobial Stewardship Program among respondents were 55.2 (SD±5.43). Astonishingly, this study revealed that only less than half (49.3%) of the respondents were familiar with the program, while cumulative mean scores of respondents' exposure towards antimicrobial stewardship were 11.2 (SD±2.74). These findings portrayed a preliminary results as this program was very new in our health society, in which a formal guideline on this program has just been launched on September 2014. More exposure in terms of educational and promotional activities should be conducted by higher authorities as they was found to significantly improved pharmacists' awareness and level of preparedness to fully execute this program. Last but not least, proper dissemination of information regarding this program should be made available and accessible in all hospitals.